American law yearbook 2015 - Tyrkus, Michael J. (Gale virtual reference library, 2016)
Annual supplement to the Gale Encyclopedia of American Law that updates and expands the content with new topics, updates, biographies of prominent figures and government appointees, and other features. Each year's edition contains the full U.S. Supreme Court docket in addition to the non-Supreme Court cases.